2008
DOI: 10.1152/ajpheart.01112.2007
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin provides pleiotropic protection against pulmonary hypertension, right ventricular hypertrophy, and coronary endothelial dysfunction in rats

Abstract: We recently reported that increased vascular endothelial nitric oxide production could protect against the development of monocrotaline (MCT)-induced pulmonary arterial hypertension (PAH) and right ventricular hypertrophy (RVH) in rats (32). The present study investigated whether the pleiotropic action of 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors in upregulating endothelial function could also protect against the MCT-induced end-organ damages. Rosuvastatin (2 mg kg(-1) day(-1) via oral gavage) or pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 34 publications
2
43
0
3
Order By: Relevance
“…Evidence of potential therapeutic benefit from this drug class comes from a series of animal studies but there are no robust data from studies in patients (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Because the response of the RV to the increased afterload in PAH is an important determinant of patient outcome (18)(19)(20)(21), this study examined prospectively the effect of simvastatin on RV mass and function in patients with PAH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence of potential therapeutic benefit from this drug class comes from a series of animal studies but there are no robust data from studies in patients (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Because the response of the RV to the increased afterload in PAH is an important determinant of patient outcome (18)(19)(20)(21), this study examined prospectively the effect of simvastatin on RV mass and function in patients with PAH.…”
Section: Discussionmentioning
confidence: 99%
“…This spectrum of activity arises from the inhibition of isoprenoids (geranylgeranylpyrophosphate and farnesylpyrophosphate), which are essential for the post-translational isoprenylation of Rho and Ras family GTPases. Statins, in particular simvastatin, have been reported to attenuate the development of pulmonary hypertension in a number of experimental animal models (4)(5)(6)(7)(8)(9)(10)(11)(12) and to regress established pulmonary hypertension and vascular remodeling induced by either pneumonectomy and monocrotaline treatment (13) or chronic hypoxia (14). There is evidence that this is achieved through increased apoptosis as well as reduced proliferation of smooth muscle cells in obstructive vascular lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Satoh et al (7) did not observe 28-d pravastatin administration to have any significant impact on the reduction of elevated right ventricular pressure (RVP) and cardiac hypertrophy in a mono-crotaline (MCT) rat model. In opposite, Sun et al (8) showed that another hydrophilic statin -rosuvastatin when given especially for early protection against PH development had positive impact on myocardial hypertrophy and reduction of pulmonary pressure. Also, the benefits of adding statins to a conventional regimen have been investigated in several studies.…”
mentioning
confidence: 99%
“…Such effects, primarily concerned with improving or restoring endothelial function, inhibiting the proliferation and migration of vascular smooth muscle cells or reducing myocardial mass and fibrosis (5), have been demonstrated mainly for simvastatin, one of the most »popular« statins, with pleiotropic activity being confirmed clinically in a number of multicenter trials (6). The influence of other statins, including less lipophilic ones, has only been assessed in very few experimental studies (7)(8)(9)(10). Satoh et al (7) did not observe 28-d pravastatin administration to have any significant impact on the reduction of elevated right ventricular pressure (RVP) and cardiac hypertrophy in a mono-crotaline (MCT) rat model.…”
mentioning
confidence: 99%